The Photophysics of Pyridine-Derivatized ortho-, meta-, and para-Dibutylamino Cruciforms - Hinderer, Florian; Bunz, Uwe H. F. (Chemistry - a European journal, 2013)
The photophysical properties of a series of para-substituted donor-acceptor cruciform fluorophores (p1-4) were investigated and compared with their meta and ortho isomers (m1-4 and o1-4). The structural variations were found to have a significant effect on the solvatochromism, fluorescence quantum yields (Φfl), fluorescence lifetimes (τfl), and response upon addition of trifluoroacetic acid. The observed spectral shifts in absorption and emission caused by protonation of the cruciforms make them promising candidates as chemosensors. Additional computational studies provided more insight into the electronic structure of the systems.
Gesehen am 25.05.2021